Estimation of Probiotic Lactobacilli Drug Resistance - N. L. Bruslik; D. R. Akhatova; A. A. Toimentseva; S. R. Abdulkhakov; O. N. Ilyinskaya; D. R. Yarullina (Антибиотики и Химиотерапия)
An actual problem of analysis of probiotic lactobacilli resistance to antibiotics and other drugs used in the treatment of gastro-intestinal disturbances has been for the first time solved. The levels of resistance of 19 strains of Lactobacillus (14 strains of L.fermentum, 4 strains of L.plantarum and 1 strain of L.rhamnosus) isolated from commercial probiotics and sour milk products to 14 antibiotics of various nature, i.e. в-lactams, aminoglycosides, macrolides, clindamycin, vancomycin, rifampicin, ciprofloxacin, tetracycline and chloramphenicol were determined. All the isolates were practically susceptible to the drugs of the first line antihelicobacterial therapy, i.e. amoxicillin and clarithromycin, that makes inexpedient the parallel use of the probiotics containing the above lactobacilli in the treatment of gastritis and gastric ulcer, despite the lactobacilli antagonism with respect to Helicobacterpylory. Lactobacilli are as well resistant to mesalazin and can be used for correction of dysbiosis in inflammatory affections of the intestine.